1993
DOI: 10.1002/app.1993.070480908
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of the metal‐binding properties of chitosan through synthetic addition of sulfur‐ and nitrogen‐containing compounds

Abstract: SY N 0 PSISSeveral new chitosan derivatives were synthesized with the intent of forming polymers that could be used in hazardous waste remediation as toxic metal-binding agents in aqueous environments. The ability of these derivatives to bind Cu2+, Pb2+, Cd2+, and Fez+ was tested and compared to chitosan. Four of the new compounds, the products of the reaction of chitosan with mercaptosuccinic acid, thiirane, pyridoxal hydrochloride, and succinamide, show promising results as binding agents for the above metal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
21
0
1

Year Published

1997
1997
2008
2008

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 6 publications
0
21
0
1
Order By: Relevance
“…The pH rise could be due to the unfolding of the chitosan chain, breaking of internal hydrogen bonds, and the protonation of the amine group by water. 25 In the majority of previous pH studies, researchers have not indicated whether the pH had been simply adjusted initially or whether it had been monitored and adjusted throughout the course of the experiment. Because of this pH rise in chitosan suspensions in water, close monitoring and adjustment of pH is necessary to establish the pH range in which metal ion binding is favored.…”
Section: Introductionmentioning
confidence: 99%
“…The pH rise could be due to the unfolding of the chitosan chain, breaking of internal hydrogen bonds, and the protonation of the amine group by water. 25 In the majority of previous pH studies, researchers have not indicated whether the pH had been simply adjusted initially or whether it had been monitored and adjusted throughout the course of the experiment. Because of this pH rise in chitosan suspensions in water, close monitoring and adjustment of pH is necessary to establish the pH range in which metal ion binding is favored.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12] Many graft copolymers of chitosan and vinyl monomers were synthesized and evaluated as flocculents, paper strengtheners, drug-releasers, and so on. [13][14][15][16][17][18][19] Conventionally vinyl monomers are grafted onto chitosan using various redox systems. 20 -23 Concurrent homopolymer formation is the main constraint in graft copolymerization, leading to low grafting yield.…”
Section: Introductionmentioning
confidence: 99%
“…4 In particular, its adsorption properties have attracted much attention as a potential hazardous waste remediation material, because chitosan has a demonstrated ability to bind transition metal ions especially heavy or precious metal ions. [5][6][7][8][9][10] For its particular molecular structure, crown ethers have good complex selectivity for many metal ions, but they are expensive and unrecyclated easily after used; therefore, its application was limited. If crown ethers were grafted in chitosan chain to give chitosan-crown ethers containing double structures and properties of chitosan and crown ethers, it can be predicated that these novel chitosan derivatives have wide-rang-ing applications for the separation and concentration of heavy or precious metal ions.…”
Section: Introductionmentioning
confidence: 99%